Diversity of the Anisoptera & Zygoptera (Odonata: Insecta) of Swat, Pakistan - Attaullah,M. (2023)
Abstract Odonates are important biological control agents for the control of insect pests and insect disease vectors of medical and veterinary importance. The present study was conducted to evaluate the odonate fauna of Swat, Pakistan from March to October 2019. A total of 200 specimens of odonates were collected from diverse habitats. The collected specimens of the order Odonata belonged to 5 families, three families of suborder Anisoptera namely Libellulidae, Gomphidae and Aeshnidae while two families of suborder Zygoptera (Chlorocyphidae and Coenagrionidae). The specimens were categorized into 12 genera and 22 species. Libellulidae was the dominant family (n = 138) accounting for 69% of the odonate fauna. Orthetrum was the dominant genus (n = 73) of suborder Anisoptera accounting for 36.5% of the odonate fauna. The least dominant genera were Anax, Paragomphus and Rhyothemis (n = 5 each) accounting each for 2.5% of the odonate fauna. In Zygoptera, the dominant genus was Ceriagrion (12.5%) and the least dominant genus was Ischnura (6%). Pantala flavescens (Fabricius, 1798) was the most abundant odonate species in the study area recorded from all surveyed habitats. Shannon Diversity Index (H) was 2.988 and Simpson Diversity Index (D) was 0.95 for the collected odonate fauna. The highest abundance of Odonata was recorded in August, September and May while no odonate species were recorded in January, February, November and December. Lotic water bodies were the most suitable habitats with abundant odonate fauna. Anax immaculifrons (Rambur, 1842) was the largest sized odonate species having a wingspan of 53.2±1.63 mm and body length of 56.3 ± 0.4 mm. The present study shows the status of odonate fauna of Swat, Pakistan in diverse habitats and seasonsonal variation throughout the year. Further work is recommended to bridge the gaps in the existing literature.